Programming Aide for the Visually Impaired - Mercy Rajaselvi V, Jane Gloria F, Mohitha V, Guhan Selvarajan (International Journal of Advanced Science and Technology, 2020)
As our society rapidly improves its standard of living and education, it is imperative that even the less fortunate among us are benefited by the various advancements proposed by technology. More and more tools and techniques are being designed for the sole purpose of being accessible to those with disabilities. It is a commonly known fact that the differently abled are not provided with proper education and educational tools because of the lack of proper infrastructure or equipment to help them.  A survey shows that 0.5% of the student population are differently abled. Among those students, their choice of course is usually Arts and Science since there is very little scope for the differently abled in the field of technical studies like computer coding. In recent years, various technologies have been developed that can be used to teach computer programming to differently abled students. But none of these specifically target the visually challenged students. They usually present certain drawbacks that do not enable easy learning and usage. There is no concentration in code writing. Technological tools must be developed in such a way that they are accessible by all, even the differently abled population. This should also apply to coding editors. Tools that aim to help the visually impaired students to code must do so without costly equipment or extreme changes to existing systems. It should be a software solution so that it can be easily implemented. Such solutions can also be commercialized to help easier coding for industry experts. Enabling the visually impaired students to easily access computer programming tools and techniques will open new opportunities for them. This paper focuses on the use of voice-enabled programming editors that will enable hands-free coding. The proposed system aims to provide a starting platform for the visually impaired person to start coding in Python language. The system takes the user voice as the input, performs speech to text conversion. The converted text is then processed and mapped to proper syntax. The dictated code is generated in the Python IDE. The code is then tested for proper semantics and also provides an option to read back the code using text to speech converter in order to verify the correctness of the code. The system will aid in error correction by navigating to the line containing the error and provide feedback.